Factores organizacionales y tecnológicos que influyen en la productividad del teletrabajo en los bancos con operaciones internacionales en el Perú dentro de la crisis sanitaria del COVID-19 - Hernandez Garces, Luis Enrique (2022)
This study aims to demonstrate the influence that technological and organizational factors have on the productivity of the Peruvian banking sector with the adoption of teleworking as a new work modality as a consequence of the pandemic caused by COVID-19 and social confinement. The research arose from the problem of teleworking as a result of the COVID-19 crisis. A theoretical framework was used with the most important factors involved in teleworking, organizational and technological. In addition, a theoretical model explains the productivity of teleworking due to the efficiency and quality of the teleworkers work-life. Then, these two theories are taken as the basis for relating the influence of our independent variables, which are the factors and their dimensions, on our dependent variable, which is productivity. The applied methodology was quantitative and qualitative. For the quantitative part, surveys were used for a sample of 307 teleworkers from the four leading banks in Peru (Scotiabank, BCP, BBVA and Interbank) and the Development Bank of Latin America (CAF). For the qualitative part, the in-depth interviews obtained responses from the managers and directors of these banks. The results of the field study confirm the hypotheses on each dimension analyzed within the variables, except the access to the internet and virtual platforms, which was not shown to have a direct influence on productivity, among the others variables are advances in ICT, organizational motivation and organizational communication; and how these directly influence the efficiency and quality of working life than the main dimensions that generate productivity within banks with international operations in Peru during the current health crisis.